Unsuspecting souls : the disappearance of the human being - Sanders, Barry, 1938- (Berkeley : Counterpoint : Distributed by Publishers Group West, 2009)
"In Unsuspecting Souls, Barry Sanders examines modern society's indifference to the individual. Beginning with the Industrial Revolution, when care for human beings began to disappear slowly, and ending with the modern era, when societal events require less person-to-person interaction and introduce radical changes in common attitudes toward death and life, Sanders laments that what makes us most human is slowly dying. Our days are filled with a continuous bombardment of 'information' that demands our attention and brings us out of our world and into a sterile one of inhumanity and abstraction. We've also lost the original sense of a collective consciousness. This loss has been culminating for two centuries now, dating back to the rise of European powers and worldwide colonization. We pick our poisons among several forms of radical fundamentalisms, each one not only a threat to the other but a threat to humanity itself."--From publisher description.
Introduction: Pictures at a deposition -- What is life? -- When death died -- A couple of Sarahs later -- No one's dead -- There is only life -- Coney Island and the mind -- The Draculated cat.
Includes bibliographical references and index.
Keywords: Mass society -- History; Individuality -- History; Conformity -- History; Social problems -- History; Popular culture -- History